Synthesis and Characterization of Some New 2-Amino-4- (4'-substituted)-6-(4''-substituted)diphenyl Pyrimidines - Hasan, Aurangzeb; Khaleeq, Musfirah; Riaz, Uzma (Asian Journal of Chemistry, 2010)
Synthesis and characterization of some novel 2-amino-4-(4'-substituted)-6-(4''-substituted)- diphenyl pyrimidines has been carried out by the conversion of variably substituted acetophenones and benzaldehydes into corresponding chalcones followed by cyclization with guanidine hydrochloride in the presence of an oxidizing agent.